Libraries and the 2030 Agenda: The Portuguese Case - Gama Merabe Carvalho Ferreira da (Libri)
This article studies Portuguese libraries that have won the “Libraries: Development and the 2030 Agenda” award promoted since 2018 by the Portuguese Association of Librarians, Archivists, Information and Documentation Professionals together with the General Directorate of Books, Archives and Libraries. The aim is to identify the common characteristics of the libraries that have won the award so that these success stories can help other libraries with guidance on what characteristics they should develop in their teams in order to develop projects and actions that contribute to a more sustainable world. The method used is grounded theory with human analysis and Iramuteq software. Six common characteristics were found among the libraries: partnerships, teamwork, a focus on the community, projects linked to the territory, support and alignment with senior management regarding the SDGs, and funding. These characteristics together can lead to successful projects in the context of the 2030 Agenda and promote innovative services. It is also desirable that the projects developed are constantly monitored and evaluated. We conclude that libraries that want to develop projects for the 2030 Agenda should invest in these characteristics.